THU0281 Evaluating S100A12 as a Serum Biomarker for Inflammatory Disease Activity in Pediatric Primary Chronic Vasculitides Using a Novel Monoclonal Sandwich Elisa. (9th June 2015) - Armaroli, G.; Brown, K.; Cabral, D.; Benseler, S.; Föll, D.; Kessel, C.
Abstract : Background: Primary chronic vasculitides are rare organ- to life-threatening diseases of unknown pathogenesis. Due to the heterogeneous clinical manifestations and lack of established diagnostic criteria diagnosis remains challenging. Evaluations of biomarkers that can distinguish patients by disease activity are crucial to improve disease management. The granulocytic damage associated molecular pattern (DAMP) protein S100A12 has been suggested to drive pathogenesis in vascular inflammation (1). It has been reported elevated in giant cell arteritis patients' serum (2) and to correlate with disease activity, response to treatment and prognosis in Kawasaki disease (3). Objectives: In this study we aimed at evaluating S100A12 as a serum biomarker of disease activity in pediatric primary chronic vasculitis using a novel highly sensitive monoclonal sandwich ELISA. Methods: We developed a sandwich ELISA detecting a defined epitope with solvent accessible surface presence on all S100A12 quarternary structures. This ELISA was used to analyze S100A12 serum levels in samples of healthy controls (HC, n=42) as well as 39 children and adolescents with chronic vasculitis enrolled in the Pediatric Vasculitis Initiative (PedVas). PedVas (ClinicalTrials.gov: NCT02006134 ) aims at collecting retro- and prospective clinical data from young (max 20 years) vasculitis patients. Blood, urine, and saliva are collected at time-of-diagnosis, post-induction, 12-month post diagnosis, disease flare and remission/post-flare. For retrospectively recruited patients, sampling is restricted to disease flare and remission/post-flare. Results: Except for samples collected during remission, serum S100A12 levels were significantly elevated in vasculitis patients compared to HC at all sampling time points. Follow-up samples revealed S100A12-levels to drop after therapy-induction while re-increasing during flare. No significant differences in S100A12 titers in ANCA-associated vasculitis (AAV) vs none-AAV were observed. However, according to S100A12 serum levels as well as correlations between S100A12 and the Pediatric Vasculitis Activity Score (PVAS), none-AAV patients appeared to respond better to anti-inflammatory therapy. S100A12 also correlated with patients' CRP. However, elevated S100A12 serum levels were able to identify patients with high PVAS score or damage index, which were missed by CRP alone. Conclusions: The results from our pilot study suggest serum S100A12 quantification to support disease monitoring in pediatric primary chronic vasculitis. References: Hofmann Bowman M, et al. (2010) S100A12 mediates aortic wall remodeling and aortic aneurysm. Circulation research 106(1):145-154. Foell D, et al. (2004) Early recruitment of phagocytes contributes to the vascular inflammation of giant cell arteritis. The Journal of pathology 204(3):311-316. Foell D, et al. (2003) S100A12 (EN-RAGE) in monitoring Kawasaki disease. Lancet 361(9365):1270-1272. Disclosure of Interest: None declared